2019
DOI: 10.20533/ijehis.2046.3332.2019.0021
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perception and Parent-Adolescent Communication on Sexual Health in Southwest Nigeria

Abstract: The issue of family intervention in adolescent's sexual health has become a global health concern because of increased sexual risk-taking behaviour among adolescents. A research question was raised to elicit information from respondents on parents' perception on communication on adolescents' sexual health. Also, one hypothesis was generated to examine the relationship between parents' perception and communication on adolescents' sexual health. The descriptive research of the survey type was adopted. Seven hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A.S. Shehu [15], stated that the framework conceptualized the construction procurement management knowledge as a conglomerate of knowledge (system) that is made up of units of knowledge aligned to accomplish a construction project. Ogunsanmi O, E [16], evaluated the effects of procurementrelated factors on project performance by using the snowballing sampling technique for 40 selected construction organizations. The results of the study indicated that procurement selection criteria, project characteristics, time, cost, quality, and external environmental factors have effects on project performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A.S. Shehu [15], stated that the framework conceptualized the construction procurement management knowledge as a conglomerate of knowledge (system) that is made up of units of knowledge aligned to accomplish a construction project. Ogunsanmi O, E [16], evaluated the effects of procurementrelated factors on project performance by using the snowballing sampling technique for 40 selected construction organizations. The results of the study indicated that procurement selection criteria, project characteristics, time, cost, quality, and external environmental factors have effects on project performance.…”
Section: Literature Reviewmentioning
confidence: 99%